India's Internal Labor Migration Paradox : The Statistical and the Real - Nayyar, Gaurav; Kim, Kyoung Yang (World Bank, Washington, DC, 2018)
Internal labor migration rates in India have been largely static and low in recent times compared with those in other countries. This is a cause for concern because internal migration for economic reasons can promote the agglomeration of economic activity in more productive locations and directly contribute to reducing poverty through remittances. New evidence based on the India Human Development Survey, which provides a more recent source of data compared with the Census and other household surveys, shows that labor mobility is higher than previously estimated -- the stock of labor migrants increased from 16 million in 2004-05 to 60 million in 2011–12. The absolute number of circular migrants, at more than 200 million in 2011-12, is also much higher than previously documented estimates. Tracking the same households between 2004–05 and 2011-12, empirical analysis based on the India Human Development Survey highlights several socioeconomic factors associated with the migration decision: household income, the availability of information, as well as community networks in source and destination areas. There is also a possible administrative dimension to interstate migration barriers, owing to domicile provisions for work and study, lack of portability of social benefits, and legal and other entitlements upon relocation.